Moderating effects of government support on the relationship between organizational innovativeness, culture and sustainable construction among Malaysian contractors - Bamgbade, Jibril Adewale (2016)
Drawing upon organizational readiness for change and resource-based view theories, this study examined the role of government support in moderating the effects of organizational innovativeness and organizational culture on sustainable construction among Malaysian large contractors (the G7 contractors). A total of 172 contractors from the eleven states in peninsula Malaysia participated in the survey. The data collected were initially screened using SPSS (version 21), while Partial Least Squares Structural Equation Modeling (PLS-SEM) algorithm and bootstrap techniques were employed to test the hypothesized paths in this study. Specifically, the results indicated that the extent of sustainable construction among Malaysian large contractors is high (mean score: 3.95). The empirical evidence also supported the hypothesized direct effects of organizational innovativeness and organizational culture on sustainable construction. However, government support was found to be negatively but significantly related to sustainable construction. There also was a stronger positive relationship between organizational innovativeness and sustainable construction, to such an extent that this relationship becomes stronger (i.e. more positive) for contractors that are being aided by the government than it is for those that are disadvantaged in that regard. Similarly, the result regarding the moderating effect of government support on the relationship between organizational culture and sustainable construction was supported. Generally, these findings supported the view that government support has a strong contingent effect on the influence of contractors’ innovativeness and culture on sustainability adoption in construction project execution. Therefore, to enhance sustainable construction adoption, more efforts are suggested to be applied to developing and utilising organizational innovativeness and organizational cultural dimensions, while more government support is also encouraged. Some limitations of the study are indicated, suggesting opportunities for future research.